The effectiveness of flower strips and hedgerows on pest control, pollination services and crop yield: a quantitative synthesis - Matthias Albrecht; David Kleijn; Neal M. Williams; Matthias Tschumi; Brett R. Blaauw; Riccardo Bommarco; Alistair J. Campbell; Matteo Dainese; Francis A. Drummond; Martin H. Entling; Dominik Ganser; G. Arjen de Groot; et al. (Ecology Letters, 2020)
Floral plantings are promoted to foster ecological intensification of agriculture through provisioning of ecosystem services. However, a comprehensive assessment of the effectiveness of different floral plantings, their characteristics and consequences for crop yield is lacking. Here we quantified the impacts of flower strips and hedgerows on pest control (18 studies) and pollination services (17 studies) in adjacent crops in North America, Europe and New Zealand. Flower strips, but not hedgerows, enhanced pest control services in adjacent fields by 16% on average. However, effects on crop pollination and yield were more variable. Our synthesis identifies several important drivers of variability in effectiveness of plantings: pollination services declined exponentially with distance from plantings, and perennial and older flower strips with higher flowering plant diversity enhanced pollination more effectively. These findings provide promising pathways to optimise floral plantings to more effectively contribute to ecosystem service delivery and ecological intensification of agriculture in the future.

Nectar from oilseed rape and floral subsidies enhances longevity of an aphid parasitoid more than does host honeydew - Yann-David Varennes; Stéphane Boyer; Steve D. Wratten (BioControl, 2016)

Pyrosequencing of prey DNA in faeces of carnivorous land snails to facilitate ecological restoration and relocation programmes - Benjamin R. Waterhouse; Stéphane Boyer; Steve D. Wratten (Oecologia, 2014)

Molecular mapping of qualitative and quantitative loci for resistance to Leptosphaeria maculans causing blackleg disease in canola (Brassica napus L.) - Rosy Raman; Belinda Taylor; Steve Marcroft; Jiri Stiller; Paul Eckermann; Neil Coombes; Ata Rehman; Kurt Lindbeck; David Luckett; Neil Wratten; Jacqueline Batley; David Edwards; et al. (Theoretical and Applied Genetics, 2012)

The importance of viticultural landscape features and ecosystem service enhancement for native butterflies in New Zealand vineyards - Mark Gillespie; Steve D. Wratten (Journal of Insect Conservation, 2012)

Habitat manipulation to mitigate the impacts of invasive arthropod pests - Mattias Jonsson; Steve D. Wratten; Doug A. Landis; Jean-Marie L. Tompkins; Ross Cullen (Biological Invasions, 2010)

Zinc sulfate and atrazine toxicity to the marine harpacticoid copepod Robertsonia propinqua - Lisa A. Hack; Louis A. Tremblay; Steve D. Wratten; Guy Forrester; Vaughan Keesing (New Zealand Journal of Marine and Freshwater Research, 2008)
Nauplii and adults of Robertsonia propinqua , a marine sediment‐dwelling copepod, were used in 96‐h static range‐finder toxicity tests to assess the lethal concentration at which 50% of test organisms are killed (LC 50 ) by atrazine (a herbicide) and zinc sulfate. Atrazine and zinc sulfate were used at concentrations near LC 50 values published for crustaceans. LC 50 values for R. propinqua nauplii were 1.5 mg/litre for atrazine and 1.7 mg/litre for zinc sulfate, respectively. For R. propinqua adults, the corresponding values were 31.8 mg/ litre for atrazine and 2.7 mg/litre for zinc sulfate. Robertsonia propinqua nauplii were more sensitive than adult life stages to exposure to both compounds, implying that the juvenile life stages are more sensitive to pollutants. These tests provided some evidence that both atrazine and zinc sulfate may be affecting the reproduction of R. propinqua owing to the reduced juvenile survival rates in the acute tests. The data for atrazine and zinc sulfate have important implications for the development of R. propinqua as a bioindicator of aquatic contamination. The range‐finding LC 50 results provide the basis for the determination of a realistic environmental concentration gradient for application in future definitive LC 50 and chronic full life cycle toxicity tests.

Expression of cry1Ac9 and cry9Aa2 genes under a potato light-inducible Lhca3 promoter in transgenic potatoes for tuber moth resistance - Sathiyamoorthy Meiyalaghan; Jeanne M. E. Jacobs; Ruth C. Butler; Steve D. Wratten; Anthony J. Conner (Euphytica, 2006)

The population consequences of natural enemy enhancement, and implications for conservation biological control - John Kean; Steve Wratten; Jason Tylianakis; Nigel Barlow (Ecology Letters, 2003)
We explore models for the management of invertebrate pests by enhancing the efficacy or local abundance of existing natural enemies. Different aspects of natural enemy biology had different effects on prey density. Enhancement of enemy search rate or prey conversion efficiency showed the greatest potential for reducing prey density, while maximum consumption rate by predators, and parasitoid fecundity, had less effect. The effect on prey density of increased natural enemy longevity depended on its interaction with other parameters. The degree of manipulation needed to achieve a given reduction in prey populations was largely determined by the enemy's potential reproductive rate. Spatial ‘‘attraction’’ of enemies to a target site had an almost linear effect on local prey density. We conclude that successful conservation biological control benefits from a directed approach, targeting the most important aspects of natural enemy ecology, and that there is considerable potential for further research in this area.

Field boundaries as barriers to movement of hover flies (Diptera: Syrphidae) in cultivated land - Steve D. Wratten; Mike H. Bowie; Janice M. Hickman; Alison M. Evans; J. Richard Sedcole; Jason M. Tylianakis (Oecologia, 2003)

Sensitivity of aquatic life stages of Xanthocnemis zealandica (Odonata: Zygoptera) to azinphos‐methyi and carbaryi - Sonke Hardersen; Steve D. Wratten (New Zealand Journal of Marine and Freshwater Research, 2000)
The susceptibility (48‐h LC 50 values) of aquatic life stages of Xanthocnemis zealandica McLachlan to azinphos‐methyi and carbaryi was investigated. The LC50 values of azinphos‐methyi did not correlate with instar. The most susceptible stage was instar 7 (LC 50 value: 26.6 ppb), and the least susceptible were instars 2 (LC50 value: 50.2 ppb) and 13 (LC 50 value: 45.1 ppb). In contrast, LC 50 values for carbaryi were positively related to larval instar (instar 2: LC 50 value: 156.6 ppb; instar 13: LC 50 value: 760 ppb). Damselfly eggs were exposed to insecticide solutions (azinphos‐methyi: control, 0.04, 0.4, 4, and 40 ppb; carbaryi: 0.6 b and 6, 60, and 600 ppb) and hatching success evaluated. Only carbaryi at 600 ppb reduced hatching success significantly. Although the investigation on eggs was carried out at a higher temperature than the LC 50 experiments it can be concluded that the egg stage is more resilient to both insecticides than the larval stages.

The Effects of Carbaryl Exposure of the Penultimate Larval Instars of Xathocnemis Zealandica on Emergence and Fluctuating Asymmetry - Sönke Hardersen; Steve D. Wratten (Ecotoxicology, 1998)